USING ISLAMIC VIDEOS ON YOUTUBE TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS' ENGLISH VOCABULARY MASTERY - Jasmia, Jasmia; Anwar Korompot, Chairil; Atmowardoyo, Haryanto Atmowardoyo (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This research  aims  to  discover  whether  applying Islamic  videos on YouTube  might increase junior high school students' English vocabulary mastery. This research used a pre-experimental method with a one-group pre-test and post-test design and a questionnaire. The study population was 40 grade 8 students at SMP IT Nurul Fikri Makassar, South Sulawesi, in the 2021–2022 academic year. The respondents were recruited using a random sampling technique. The research instruments were a vocabulary test administered as a post-test and a pre-test, and a questionnaire. In analyzing  the data,  descriptive  statistics  was  used.  The  post-test  mean  score  was 84.5455; which shows that the post-test mean score was more significant than the pre- test mean score (68.6364). Of the percentage of students’ perceptions while using Islamic videos on YouTube, 85% answered yes, and only 15% answered no. Furthermore, the value of this study (0.001) was lower than the alpha level (0.05). These mean that H1 is accepted and H0 is rejected. Consequently, Islamic videos on YouTube could be used as medium to improve the students' English vocabulary mastery in grade 8 of SMP IT Nurul Fikri Makassar.